Augmented medial rectus recession in the management of esotropia. Issue 11 (November 1986) - Willshaw, H E; Mashhoudi, N; Powell, S
Abstract : Forty-six children awaiting surgery for concomitant esotropia were placed into two matched groups. One group received bilateral medial rectus recessions, while the second group received augmented bilateral medial rectus recessions. By recession the conjunctiva and subconjunctival tissue in addition to the medial rectus we consistently increased the correction obtained. With bilateral medial rectus recession to correct large angle esotropia application of the augmented technique is more likely to provide a full correction.